"It used to be...but now..." An Oral History of Lebanon, Oregon, and Surrounding Areas - Jane White; Toni Redmond; Patty Mills; Tammie Escano; Jolene Gibson; Mark Cunningham; Brenda McElhenney (1978)
Oral History of Lebanon, Oregon, and Surrounding Areas